Da novela ao filme: processos adaptativos e intermidiáticos na articulação entre história de iniciação e espaço em The Cement Garden. - Veras, Lucas Neves (2021)
The present dissertation aims to analyze the initiation story in articulation with space in the novel The cement garden (1978), by Ian McEwan, in comparison with its cinematographic adaptation, named after the same name, directed by Andrew Birkin in 1993. Since we are investigating a literary text in dialog with its filmic adaptation, it is important to outline how each language is used in order to build an initiation story. For this purpose, we will take in consideration the potentialities of both audiovisual and literary languages in the light of the adaptation and intermedial theories, with texts by Rajewski (2012), Straumman (2015) and Gaudreault e Marion (2012). Since we are dealing with a context of an initiation story, in which subjectivities are questioned and deconstructed, in which we can also see the loss of innocence, Marcus (1976) and Lacan (1977) will be used so as to help one to understand the process. Both works raise important issues about the consequences that orphanhood and isolation – when present in a context of an initiaton story – might provoke; for this reason, we also draw on Culler (1999) to complement the discussion about the construction of an identity, as well as on theoreticians who discuss the issue of space.